Les voyageuses françaises au prisme de la bibliographie annuelle de l’histoire de France (de 1970 à 2010) - Isabelle Havelange (Genre & Histoire)
This article uses the Bibliographie annuelle de l’histoire de France (BAHF) to explore the past thirty years of scholarship on women’s travel highlighting the French contributions to a field that has been dominated by Anglo-American scholars. It brings to light the writings of women travelers, which have been often understudied and neglected, and establishes a typology of their travels from the Middle Ages to the 20th century.  The article includes a list of 135 French women travelers with the citations found in the BAHF.